Educação de adultos maduros no processo de formação de condutores : um estudo de caso comparativo a partir dos resultados de provas teóricas - Kist, Silvério (2018)
This dissertation analyzed how the formation of mature adult students, people aged under 40 years. The study was carried out in two Driver Training Centers where different results were found in the theoretical tests of the city of Porto Alegre. Based on the secondary data from the State Department of Traffic system, with the respective finding that has the lowest and the highest ratio of test results, I analyzed theories that reflected the best practices in adult education and adult life, I established some questions based on the central question of the research, which was how the training of mature adult drivers in Driver Training centers with different results in the theoretical tests, based on theories that deal with how the education of these adults happens best. In addition to the quantitative data analyzed, I conducted interviews in both centers, in CFC1 with the theoretical traffic instructor and the teaching director and in CFC 2 with two theoretical instructors and a teaching director. I analyzed the interviews comparing the statements of the interviewees with the theories of adult education. I have found that the best results for mature adults in CFC 1 are directly related to the practices of their instructor who uses various aspects related to the training of this audience, even though it does not indicate the theoretical awareness of why they use such practices. The study showed that educational actions aimed at mature adults are still little explored by the Driver Training Centers and that there is a possibility of significantly improving the training of these people, future drivers, based on theories already available in the area of Education, to qualify teaching practices in the teaching of mature adults, much more appropriate to these people.